Breast Cancer Prognosis Using Learning Vector Quantization Neural Network Technique - Abdul Hameed, W.; Das, Raja; Jaiswal, Jitendra (International Journal of Engineering and Technology, 2018)
A suitable treatment coming after surgery is very much motivated by prognosis - the speculated outcome of the disease. Now-a-days improving prognostic prediction is a challenging task to the doctors. This paper presents prognosis for the breast cancer issues by applying Neural Network Architecture with the dataset for Wisconsin Prognostic Breast Cancer. The accuracy is evaluated by adopting algorithm for Kohonenâ€™s first issue of Learning Vector Quantization to predict the recurrence of the disease within 2 years or beyond and also within 5 years or beyond.Â Â